Factors affecting economic growth of the Southern key economic region - Nguyễn Lê Hoàng Thụy Tố Quyên; Ngô Thị Cẩm Hường (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2022)
This study was conducted to explore the determinants of economic growth of the provinces in the Southern key economic region. Based on a sample of 08 provinces in the period 2005 - 2019, panel data estimations such as Pooled OLS regression, Fixed Effect (FEM), Random Effect (REM), and Feasible Generalized Least Square (FGLS) were applied. After testing and comparing the effectiveness of these methods, the authors found that the FGLS is superior. The research results provide empirical evidence that the economic growth of the key Southern provinces is positively influenced by exports, the proportion of the urban population, the level of education, and the ability to develop information technology. The findings imply the policies to push international trade, attract foreign direct investment, accelerate the development of information technology, improve labor quality and boost the urbanization process.